Metastatic ovarian carcinosarcoma in a patient undergoing in-vitro fertilization: A case report. (March 2023) - Flint, Matthew; Velasquez, Jessica; Carr, Caitlin; Kolev, Valentin; Zakashansky, Konstantin
Abstract: Introduction and importance: Ovarian carcinosarcomas (OCS) are highly aggressive tumors containing both carcinomatous and sarcomatous elements. Patients are typically older postmenopausal women who present with advanced disease, however rarely young women can be affected. Case presentation: A 41-year-old woman undergoing fertility treatment was found to have a new 9–10 cm pelvic mass on routine transvaginal ultrasound (TVUS) 16 days after embryo transfer. Diagnostic laparoscopy revealed a mass in the posterior cul-de-sac that was surgically excised and sent to pathology for evaluation. Pathology was consistent with carcinosarcoma of gynecologic origin. Further work-up revealed advanced disease with apparent rapid progression. Patient underwent interval debulking surgery after four cycles of neoadjuvant chemotherapy with carboplatin and paclitaxel with final pathology consistent with primary ovarian carcinosarcoma and complete gross resection of disease. Clinical discussion: In the setting of advanced disease neoadjuvant chemotherapy with a platinum-based chemotherapy regimen followed by cytoreductive surgery is a standard approach to treatment of OCS. Given the rarity of disease, most data regarding treatment has been extrapolated from other forms of epithelial ovarian cancer. Specific risk factors for disease development of OCS including the long-term effects of assisted reproductive technology remain understudied. Conclusion: While OCS are rare highly aggressive biphasic tumors that primarily affect older postmenopausal woman, we present a unique case of OCS incidentally found in a young woman undergoing fertility treatment via in-vitro fertilization. Highlights: Ovarian carcinosarcoma can rarely affect reproductive-age woman. Ovarian carcinosarcoma is an aggressive neoplasm with rapid progression of disease. Cytoreductive surgery with platinum-based chemotherapy regimen is the main therapy. Additional adjuvant therapies continue to be studied. Effects of assisted-reproductive technology on ovarian cancer remain understudied.